Urban Regeneration Policies, Urban Revitalization and the End of Poverty - Emília Malcata Rebelo (2003)
In this paper it is proposed a set of integrated tools designed to support urban regeneration policies in order to solve desertification processes in the older city centres, that allows the achievement of concrete solutions to the problem of poverty, enhancing local communities participation and involvement in socio-economic and cultural urban initiatives. It is presented the case study of the Oporto city (Portugal), where the obsolete law of rents (where their levels are almost frozen at very low levels in a great percentage of rental contracts) not only does not solve the poverty problems, but also immobilises the urban regeneration processes, and (through the displacement of the housing demand to the acquisition sector) artificially improves the dwellings price levels. A model is proposed to occupy the vacant houses in the centre of Oporto city (after their renewal), by the poor people that actually live in the city centre, in very bad conditions. In this renewal process should intervene joint ventures between the municipal authorities and the private initiative, not only to assure financing, but also to enhance inhabitants involvement and participation. However, much has to be done in what concerns law and urban regulations, as well as administrative co-ordination in order to assure these proposed urban policies to be successful, not only for the local-area residents, but also to the dynamization process of the city life as a whole.